2005
DOI: 10.1007/s00432-004-0663-7
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in the manganese superoxide dismutase (MnSOD) gene and risk of breast cancer in young women

Abstract: The present study suggests that MnSOD may be implicated in breast carcinogenesis in young women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 31 publications
0
28
0
1
Order By: Relevance
“…Several studies have evaluated associations between MnSOD rs4880 genotypes and other cancers, but results have been inconsistent with respect to cancer sites and the combinatorial effects of other risk factors. Recently, Bergman et al [24] reported that the wild-type genotype (rs4880 TT) is associated with a 2.7-fold (95% CI, 2.2-5.5) increased OR indicates odd ratio; 95% CI, 95% confidence interval; MnSOD, manganese superoxide dismutase; T, thymine; C, cytosine; CIN, cervical intraepithelial neoplasia. ⁎ ORs and 95% CIs calculated by unconditional logistic regression, adjusted for age, menopausal status (premenopause versus postmenopause), number of parity (one versus two versus over three), oral contraceptive use, smoking habit (ever versus never), alcohol consumption status (ever versus never), HPV infection status.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have evaluated associations between MnSOD rs4880 genotypes and other cancers, but results have been inconsistent with respect to cancer sites and the combinatorial effects of other risk factors. Recently, Bergman et al [24] reported that the wild-type genotype (rs4880 TT) is associated with a 2.7-fold (95% CI, 2.2-5.5) increased OR indicates odd ratio; 95% CI, 95% confidence interval; MnSOD, manganese superoxide dismutase; T, thymine; C, cytosine; CIN, cervical intraepithelial neoplasia. ⁎ ORs and 95% CIs calculated by unconditional logistic regression, adjusted for age, menopausal status (premenopause versus postmenopause), number of parity (one versus two versus over three), oral contraceptive use, smoking habit (ever versus never), alcohol consumption status (ever versus never), HPV infection status.…”
Section: Discussionmentioning
confidence: 99%
“…Bergman et al (10) found significantly increased risk of breast cancer for individuals with Val/Val and Val/Ala genotypes [odds ratio (OR), 2.7; 95% confidence interval (95% CI), 2.2-5.5 and OR, 3.0; 95% CI, 1.4-6.5, respectively]. Although Silva et al (8) did not observe any significant role of this polymorphism in breast cancer susceptibility in their case-control study, when they stratified the population based on breast-feeding, they found that women who never breast-fed had a marginally decreased risk for the disease when they were having Ala allele (OR, 0.56; 95% CI, 0.32-0.99).…”
mentioning
confidence: 99%
“…Although Silva et al (8) did not observe any significant role of this polymorphism in breast cancer susceptibility in their case-control study, when they stratified the population based on breast-feeding, they found that women who never breast-fed had a marginally decreased risk for the disease when they were having Ala allele (OR, 0.56; 95% CI, 0.32-0.99). Although only one study evidenced significant association of Val morph with higher breast cancer risk (10) and one study revealed Ala morph with a protective role (8) Although most of the authors find association of either Val or Ala alleles with breast cancer risk either singly or together with other polymorphisms, a population-based case-control study shows no overall association of this polymorphism with this cancer (17). Egan et al (17) did not observe any significant risk for women either with Ala carrier or homozygous genotypes.…”
mentioning
confidence: 99%
“…breast cancer and 174 age-matched controls, which indicated that SOD2 TT and CT genotype could increase the prevalence rate of breast cancer (OR, 2.7; 95% CI, 2.2-5.5; OR, 3.0; 95% CI, 1.4-6.5). In the same year, Kocabaş et al (35) also carried out another case-control study, including 103 patients and 84 controls, demonstrating a similar result to Bergman et al (32); however, no significant difference about the risk of allele T and C was observed. Furthermore, the majority of other publications suggested that the SOD2 Val-16Ala could not increase or decrease breast cancer risk and survival (26)(27)(28)(29)(30)(31)33,34,(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50).…”
Section: Discussionmentioning
confidence: 64%